DAMPAK JIM CROW LAWS TERHADAP ORANG-ORANG KULIT HITAM YANG DIGAMBARKAN DALAM NOVEL THE HELP KARYA KATHRYN STOCKETT - Wonua, Indah Dewi Sartika (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This skripsi which is entitled â€œDampak Jim Crow Laws Terhadap Orang-Orang Kulit Hitam yang Digambarkan dalam Novel The Help Karya Kathryn Stockettâ€ is a study about the social life of American People in 1960 through the characters in the novel. There are two questions to be answered in this research: Howis Jim Crow Laws reflected in the novel Â andwhat is the effect of the laws to black people. The aims of this research are to analyze the reflection of the Jim Crow Laws in the novel, and to analyze what the effect of Jim Crow Laws to black people in their social life is. The writer uses theory of Aristotle, George Lukacs and Taineto describe what happened in real life of black people is reflected in a literary work. The intrinsicand extrinsic approaches are applied and the descriptive method is used in this research. The result shows that Jim Crow Laws appears through the story and produces an effect like discrimination that causes black people got treated improperlyseparated and limited in using public facilities, either these laws made white people took a benefit to put blacks in a lower class of society. Â Keywords: Effect, Jim Crow Laws, Black People, The Help